2020
DOI: 10.1371/journal.pone.0238366
|View full text |Cite
|
Sign up to set email alerts
|

Refractive stability of a new single-piece hydrophobic acrylic intraocular lens and corneal wound repair after implantation using a new automated intraocular lens delivery system

Abstract: To investigate refractive stability and characterize corneal incision repair up to 3 months after implantation of a new hydrophobic acrylic intraocular lens (IOL) with hydroxyethylmethacrylate using a new automated IOL delivery system. Methods This prospective case series included 50 eyes of 50 patients undergoing phacoemulsification and implantation of the Clareon ® CNA0T0 IOL using the AutonoMe ® automated delivery system in the Department of Ophthalmology, Keio University School of Medicine. The clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
(35 reference statements)
0
17
0
1
Order By: Relevance
“…The transient hyperopia after cataract surgery has been discussed in the previous literature, with inconsistent outcomes according to the optic-haptic design and IOL materials. [13][14][15][16] In general, one-piece IOLs show more stable ACD than three-piece IOL. 13,14 In addition, a newly introduced IOL (Clareon ® CNA0T0, Alcon Laboratories Inc) that used hydrophilic copolymer and 2-hydroxyethylmethacrylate instead of phenyl-ethyl methacrylate which is used in AcrySof IOL showed stable ACD and SE from postoperative day 1 to month 3.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The transient hyperopia after cataract surgery has been discussed in the previous literature, with inconsistent outcomes according to the optic-haptic design and IOL materials. [13][14][15][16] In general, one-piece IOLs show more stable ACD than three-piece IOL. 13,14 In addition, a newly introduced IOL (Clareon ® CNA0T0, Alcon Laboratories Inc) that used hydrophilic copolymer and 2-hydroxyethylmethacrylate instead of phenyl-ethyl methacrylate which is used in AcrySof IOL showed stable ACD and SE from postoperative day 1 to month 3.…”
Section: Discussionmentioning
confidence: 98%
“… 13 , 14 In addition, a newly introduced IOL (Clareon ® CNA0T0, Alcon Laboratories Inc) that used hydrophilic copolymer and 2-hydroxyethylmethacrylate instead of phenyl-ethyl methacrylate which is used in AcrySof IOL showed stable ACD and SE from postoperative day 1 to month 3. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since inadvertently deep insertion of the cartridge nozzle can lead to significant stretch and enlargement of the tissue, it appears that the depth guard contributes to the maintenance of wound size during IOL implantation by limiting too deep insertion [ 5 , 9 , 12 ]. Negishi et al [ 20 ] reported that AutonoMe automated delivery system with the depth guard enabled safe IOL implantation through a 2.4-mm corneal incision. In addition, the presence of depth guard seems to enhance the mechanical strength of the nozzle, which makes the cartridge more resistant to splitting and stretching by suppressing volume increases.…”
Section: Discussionmentioning
confidence: 99%
“…В ходе экспериментальных и клинических исследований показано, что новая гидрофобная акриловая ИОЛ не ассоциирована с глистенингом и поверхностным светорассеянием [11][12][13][14]. Эффективность предварительно загруженной системы доставки ИОЛ AutonoMe подтверждена в ряде работ [15][16][17][18]. Вместе с тем в литературе доступно ограниченное число работ с результатами имплантации новой ИОЛ в условиях клинической практики, а в Российской Федерации такие статьи отсутствуют.…”
unclassified